2022
DOI: 10.32672/jse.v7i4.4896
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Potensi Bahaya Di Bengkel Mobil Dwi Jaya Motor Menggunakan Pendekatan Metode Job Safety Analysis

Abstract: Bengkel Mobil Dwi Jaya Motor adalah UKM yang bergerak di bidang jasa tepatnya Bengkel Mobil, Bengkel ini melayani servise mulai dari rutin bulanan, onderstail hingga overhole. Permasalahan yang sering ditemukan di Bengkel Mobil Dwi Jaya Motor adalah para karyawan masih kurang waspada dengan adanya bahaya disekitar dan masih jarang menggunakan APD sehingga masih sering ditemukan kecelakaan kerja disaat para karyawan bekerja. Job safety analysis merupakan alat atau tools yang berguna untuk mengukur atau mengiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…The activity of changing oil has the potential to cause injury because it is not uncommon for oil to spill on the floor which can cause slipping (Arnold, 2020). According to research by Efvandi (2022), when changing oil you must use gloves and goggles because oil is a chemical which if it comes into contact with the skin continuously will have an impact on health. When changing oil you must also be careful because the work floor is usually slippery which can cause workers to injury or exposure to hot oil due to slipping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of changing oil has the potential to cause injury because it is not uncommon for oil to spill on the floor which can cause slipping (Arnold, 2020). According to research by Efvandi (2022), when changing oil you must use gloves and goggles because oil is a chemical which if it comes into contact with the skin continuously will have an impact on health. When changing oil you must also be careful because the work floor is usually slippery which can cause workers to injury or exposure to hot oil due to slipping.…”
Section: Discussionmentioning
confidence: 99%
“…Based on observations, when workers carried out battery water replacement work they did not find the personal protective equipment provided by the workshop owner. Based on research by Efvandi (2022), it was found that many workers do not use toolspersonal protection when working in the workshop. They don't care about the dangers that might occur when personal protective equipment is not used while working, this happens because they feel uncomfortable and hot when using personal protective equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Prosedur Penilaian yang dipergunakan dalam pengaplikasian metode JSA adalah melakukan proses perekapan segala faktor kemungkinan insiden bahaya yang sangat memungkinkan beresiko menyebabkan terjadinya kecelakaan kerja kemudian mengusulkan terobosan pengendalian alternatif sesuai dengan standarisasi dari K3 yang berlaku ( Ikhsan, 2022). Pengapikasian dari metode JSA memiliki berbagai keuntungan maupun manfaat serta adanya keunggulan tersendiri seperti misalnya bagaimana menyusun standar metode kerja yang tepat, strategi apa yang digunakan untuk meningkatkan produktivitas dari karyawan saat melakukan pekerjaan, merancang dan mengidentifikasi APD yang dibutuhkan selama bekerja, melakukan proses peninjuan yang diperuntukan karyawan di awal setiap aktivitas kerja yang akan dilakukan (Abidin & Mahbubah, 2021) Dalam penelitian ini , Rujukan literatur terdahulu yang menjadi referensi berasal dari hasil penelitian (Efvandi et al, 2022) yang melakukan penelitian di salah satu bengkel perbaikan kendaraan bermotor mengemukakan bahwa Dari beberapa tahapan pekerjaan yang berupa perawatan suku cadang motor , jasa servis radiator, serta penggantian oli dan pelumas mesin kendaraan ditemukan penerapan pemakaian APD yang menjadi faktor utama dalam pencegahaan dalam meminimalisir terjadinya penyebab terjadinya kecelakaan kerja. Lalu (Yulianto, 2022) yang obyek penelitiannya dilakukakan pada perusahaan yang meproduksi Outomotive spare-part menekankan bahwa pengendalian metode produksi kerja , perbaikan peralatan dan mesin kerja, Serta Implementasi dalam penerapan SOP dan pemasangan rambu peringatan yang menjadi faktor berpengaruh dalam mengurangi risiko terjadinya kejadian yang menyebabkan kecelakaan kerja.…”
Section: Pendahuluanunclassified
“…This shows that the warehousing area has a high enough hazard potential that it is necessary to pay attention to OHS risk management in this area. Efvandi, et al (2022) researched the analysis of potential hazards using the JSA method (Job Safety Analysis). The result is that during the servicing of the engine, radiator, and the stage of changing the engine oil, it was found that there are a number of hazards which include spills from hot oil, exposure to a hot radiator, and being sprayed by water from the radiator.…”
Section: Introductionmentioning
confidence: 99%